2016
DOI: 10.1111/nyas.13108
|View full text |Cite
|
Sign up to set email alerts
|

Rare tumors of esophageal squamous mucosa

Abstract: In spite of increasing incidence of esophageal adenocarcinoma in the last few decades, esophageal squamous cell carcinoma (SCC) still remains the dominant subtype of esophageal cancer worldwide. Apart from conventional SCC, some rare unconventional tumors of esophageal squamous mucosa are also well known. This study provides an introduction to these and presents a brief review of the literature, including the diagnostic and prognostic importance of each variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(140 reference statements)
1
6
0
Order By: Relevance
“…In contrast, Some previous reports have suggested that the prognosis of esophageal BSCC with locally invasive growth pattern and high proliferation activity is worse than that of typical SCC. [13][14][15] In our study, among the patients who underwent thoracic esophagectomy, the prognostic outcomes of the BSCC group were similar to those of the PSCC and MSCC group. Meanwhile, they were worse than those of the WSCC group, with a significant difference.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In contrast, Some previous reports have suggested that the prognosis of esophageal BSCC with locally invasive growth pattern and high proliferation activity is worse than that of typical SCC. [13][14][15] In our study, among the patients who underwent thoracic esophagectomy, the prognostic outcomes of the BSCC group were similar to those of the PSCC and MSCC group. Meanwhile, they were worse than those of the WSCC group, with a significant difference.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, others have detected similar outcomes. 5,[13][14][15] However, comparative analyses of survival outcomes between esophageal SCC and BSCC have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Areas of squamous cell carcinoma in situ or OSCC NOS are relative common. The tumour is highly aggressive, with a worse prognosis than OSCC NOS, even though differences are not statistically significant 32 .…”
Section: Oesophageal Squamous Carcinomamentioning
confidence: 88%
“…Esophageal squamous cell carcinoma (ESCC) accounts for a majority of esophageal cancer occurring most commonly in the upper two‐thirds of the esophagus. Rare variants of ESCC include: basaloid squamous cell carcinoma (BSCC), spindle cell (squamous) carcinoma (carcinosarcoma), undifferentiated carcinoma, verrucous (squamous) carcinoma, and carcinoma cuniculatum …”
Section: The Role Of Hpv Infection and Hpv Vaccines In Esophageal Squmentioning
confidence: 99%